Late Quaternary optically stimulated luminescence (OSL) chronology and environmental changes in the Hobq Desert, northern China. (15th March 2018) - Xu, Yantian; Lai, Zhongping; Chen, Tianyuan; Gong, Songlin
Abstract: The Hobq Desert (HD) is distributed along the south bank of the Yellow River in northern China. Proximation to the East Asian summer monsoon limit makes this desert sensitive to fluctuations of monsoonal intensity. However, environmental changes in the HD during late Quaternary are poorly known due to lack of extensive field investigation and appropriate dating materials for radiocarbon dating. In this study, seven field profiles were examined and a chronology framework based on quartz optically stimulated luminescence (OSL) was established to reconstruct environmental changes in the HD. The results suggested two possible periods when lake existed during late Quaternary. The older paleo-lake covering most part of the HD was likely to be formed before ∼160 ka and vanish at ∼100 ka, whereas the younger paleo-lake, which was much smaller, existed at ∼10 ka. The vanishment of the older paleo-lake was probably triggered by a tectonic event, while the existence of the younger paleo-lake was assumed as a response to humid climate in the beginning of Holocene. Meanwhile, the results also showed that modern desert landscape in the HD began at ∼27 ka, and kept expanding during the Holocene. The climate variations dominated the development of desert landscape in the beginning, and human activity enhanced the desertification at least since ∼1 ka.